2021
DOI: 10.3390/cells10030577
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Single-Cell Adhesion Force Kinetics and Applications

Abstract: Cells exert, sense, and respond to the different physical forces through diverse mechanisms and translating them into biochemical signals. The adhesion of cells is crucial in various developmental functions, such as to maintain tissue morphogenesis and homeostasis and activate critical signaling pathways regulating survival, migration, gene expression, and differentiation. More importantly, any mutations of adhesion receptors can lead to developmental disorders and diseases. Thus, it is essential to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 245 publications
(167 reference statements)
2
18
0
Order By: Relevance
“…spreading of cells in contact with a surface due to surface tension effects when cells are considered liquid-like [40]) since the force spectroscopy microscope actively pushes the cell onto the electrode substrate with a constant setpoint of 500 pN, and then sustains the reached z-position for the adhesion time of either 5 s or 30 s, respectively. The results were normalized to the cell-material contact area (see Materials and Methods) to exclude the influence of sheer cell size, which likely correlates with the number of formed adhesion points and therewith adhesion force itself [41]. As expected [42], we found higher values of the cell-substrate adhesion force for both cell lines on all materials for the longer contact time.…”
Section: Discussionsupporting
confidence: 55%
“…spreading of cells in contact with a surface due to surface tension effects when cells are considered liquid-like [40]) since the force spectroscopy microscope actively pushes the cell onto the electrode substrate with a constant setpoint of 500 pN, and then sustains the reached z-position for the adhesion time of either 5 s or 30 s, respectively. The results were normalized to the cell-material contact area (see Materials and Methods) to exclude the influence of sheer cell size, which likely correlates with the number of formed adhesion points and therewith adhesion force itself [41]. As expected [42], we found higher values of the cell-substrate adhesion force for both cell lines on all materials for the longer contact time.…”
Section: Discussionsupporting
confidence: 55%
“…Except for some cell types, for example, immune cells [2] , [3] and circulating tumor cells [4] , [5] , cells need to adhere to the extracellular matrix or to the surface of another cell to survive. The adhesion is influenced by both intracellular and extracellular factors such as the cytoskeleton, membrane-bound adhesion proteins, and elements of the glycocalyx [1] , [5] , [6] , [7] , [8] . The glycocalyx is a multifunctional, carbohydrate-rich layer covering the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Typical parameters of FD-curves were evaluated for the general population, and lognormal distribution was the adequate fit for these characteristic parameters. The lognormal nature of the obtained data is an important finding since most prior literature, with a relatively low number of single-cell adhesion measurements, treats experimental data as normally distributed or without the intention of addressing the nature of adhesion parameter distribution 7 , 19 , 36 , 39 . Since in a lognormal distribution a significant portion of the cells has parameters far from the mode, conclusions based on adhesion data of a low number of cells (or treating the population as normally distributed) can be heavily misleading.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, previous SCFS techniques did not produce a sufficient data output, and even low-cell-number SCFS studies suggested that the measured SCFS parameters do not follow a specific distribution. Namely, the maximal single-cell adhesion force ( F max ), adhesion energy ( E max ), and the traveled distance of the cantilever, with respect to the surface at F max ( D max ) were typically investigated 7 , 10 , 19 , 21 , 36 . Importantly, low throughput does not allow studying the distributions of large cell populations or revealing possible subpopulations.…”
Section: Introductionmentioning
confidence: 99%